2016
DOI: 10.1016/j.ibusrev.2016.01.012
|View full text |Cite
|
Sign up to set email alerts
|

The motivation of international entrepreneurship: The case of Chinese transnational entrepreneurs

Abstract: The ventures of Transnational Entrepreneurs (TEs) are a new business phenomenon, representing a fluid context in which established arrangements may be expected to change. In terms of one particular relationship, motivation has been found to be a key construct in International Entrepreneurship (IE) research, with two established features of motivation comprising entrepreneurial vision and its implementation. At the same time, nationality has been found to be a consistent influence on entrepreneurial orientation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 81 publications
3
66
0
Order By: Relevance
“…Furthermore, although researchers have utilized traditional sociological approaches to examine entrepreneurial assets of specific ethnic groups (Fairlie and Meyer 1996;Dimitratos et al 2016), the effects of transnationalism and the interplay between social, human and financial capital from home and host countries within ethnic groups remains largely unexplored but of significant importance (Ilhan-Nas et al 2011). Prior research has shown that entrepreneurs' transnationalism has resulted in new forms of cosmopolitan identity, which is still foreign in nature when compared to host countries' identities (Wong and Ng 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, although researchers have utilized traditional sociological approaches to examine entrepreneurial assets of specific ethnic groups (Fairlie and Meyer 1996;Dimitratos et al 2016), the effects of transnationalism and the interplay between social, human and financial capital from home and host countries within ethnic groups remains largely unexplored but of significant importance (Ilhan-Nas et al 2011). Prior research has shown that entrepreneurs' transnationalism has resulted in new forms of cosmopolitan identity, which is still foreign in nature when compared to host countries' identities (Wong and Ng 2002).…”
Section: Introductionmentioning
confidence: 99%
“…IE is a well-established academic domain (Coviello, McDougall, & Oviatt, 2011;Dimitratos, Buck, Fletcher, & Li, 2016). It has been a flourishing field that has contributed to expanding the discussion on entrepreneurship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, this research discovered that being bilingual and having bicultural flexibility can offer an advantage over non-immigrant entrepreneurs, particular to a new business phenomenon, transnational entrepreneurs, who are viewed as "unique animals" (Dimitratos et al, 2016). They exhibit flexibility in their foreign ventures and also actively engage in two socially embedded environments (Crick & Chaudhry, 2013).…”
Section: Other Considerationsmentioning
confidence: 96%
“…Furthermore, language is seen as a key indicator of cultural identity (Liu, 2011), and the lack of local language proficiency may present cultural adaptation problems. Moreover, with Chinese traditional Confucian culture, Chinese immigrant entrepreneurs may have to reconcile their "cultural baggage" with the harsh realities of modern economic life (Dimitratos, Buck, Fletcher, & Li, 2016;Yang & Stening, 2013).…”
Section: Recently With a Growing Chinese Immigrant Population And Thmentioning
confidence: 99%
See 1 more Smart Citation